2016
DOI: 10.1016/j.ceramint.2016.02.068
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of structural and superconducting properties of Bi-2212 textured rods by substituting sodium

Abstract: In this study, the physical and superconducting properties of Bi 2 Sr 2 Ca 1-x Na x Cu 2 O 8+ (x=0.0, 0.05, 0.075 0.1, and 0.20) textured superconducting rods prepared by a laser floating zone technique were presented. The effect of Na +1 substitution for Ca 2+ has been investigated by Xray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, transport measurements, dc-magnetization, magnetic hysteresis and magnetic critical current density. The powder XRD patterns of samples have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
(33 reference statements)
4
16
0
Order By: Relevance
“…Moreover, they clearly show a marked preferential orientation already described in the XRD data [35,36]. The effect of Na doping can be seen in the larger grain sizes of these samples, compared with the undoped ones, in a clear agreement with previously published data [28,29,37]. Especially, 0.05, 0.075, and 0.1 Na substituted samples possess larger angles between adjacent grains which imply better intergranular characteristics.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, they clearly show a marked preferential orientation already described in the XRD data [35,36]. The effect of Na doping can be seen in the larger grain sizes of these samples, compared with the undoped ones, in a clear agreement with previously published data [28,29,37]. Especially, 0.05, 0.075, and 0.1 Na substituted samples possess larger angles between adjacent grains which imply better intergranular characteristics.…”
Section: Introductionsupporting
confidence: 89%
“…In previous works, Bi2Sr2Ca1-xNaxCu2O8+bulk and textured ceramics with different Na content, prepared by a polymer solution method and the LFZ technique, respectively [28,29], have been studied. The effect of Na on the microstructural features, critical temperature TC, magnetic properties and magnetic JC have been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it has been reported that when the samples are produced by partial or total melting, Na substitution for Ca in Bi-2212 system provides high Tc values [18,39,40]. In addition, the polymer solution technique involving polyethyleneimine (PEI) is also useful to enhance the critical temperature, Tc, in the Bi-2212 phase [41].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the polymer solution technique involving polyethyleneimine (PEI) is also useful to enhance the critical temperature, Tc, in the Bi-2212 phase [41]. Moreover, Bi-2212 bulk sintered, textured and sintered-forged ceramics with different Na content, produced via PEI, Laser Floating Zone (LFZ) and sintered-forging techniques, respectively, were worked out [13,18]. In the framework of this study, we intend to investigate the magnetoresistive properties of the Bi 2 Sr 2 Ca 1-x Na x Cu 2 Ox with x=0.0, 0.05, 0.075, 0.10, and 0.15 textured materials produced via the hot-forging method.…”
Section: Introductionmentioning
confidence: 99%